PROFITABILITY OF THE CARRY TRADE STRATEGY IN THE 21st CENTURY - Koskimo, Pyry (2013)
This study analyses the profits from the foreign exchange markets using the currency carry trade strategy. The study is based on numerous previous studies that have proven that the uncovered interest parity theorem does not hold in the foreign exchange markets. The purpose of this study is to find out whether or not it would have been profitable to use the carry trade strategy to speculate against the uncovered interest parity in the foreign exchange markets during the 21st century. The data used in the empirical part of the study consists of both spot currency- exchange rates and one- and three-month interbank-interest rates. The countries chosen for the study are the ones with ten of the most actively traded currencies in the world among with three more exotic currencies. The countries are: Australia, Canada, Great-Britain, China, Iceland, Japan, Mexico, Norway, New Zealand, Sweden, Switzerland and The United States. Currencies from all of the above countries are compared against euro. The time period used in the study covers daily observations from January 2000 to April 2009. The profit of the carry trade strategy consists of two parts, the interest rate differential and the exchange rate change. These profits are calculated and analyzed. The results of the carry trade strategy are compared against the S&P 500 index. The risk factor is taken into consideration using the Sharpe ratio. The Sharpe ratios are also compared to S&P 500 index. The empirical results of this study support the hypotheses about the positive profits from the carry trade strategy. The results show that the profits from the carry trade strategy are positive in most of the positions. However, only four out of 24 positions had statistically significant positive returns. Compared to S&P 500 index all of the carry trade positions outperformed the index during the time period chosen. Considering the risk involved, half of the (12 out of 24) positions gained positive Sharpe ratios. fi=Opinnäytetyö kokotekstinä ...